Putting the genie back : solving the climate and energy dilemma - Hone, David (Climate change advisor) (Emerald Group Publishing Limited, 2017)
Climate change is one of the most pervasive yet least understood issue of our generation. Some deny it, while most are left wondering what to think and do about it. This book explores the climate issue from its very beginnings through to the end of end of the 21st Century and looks in depth at the transition challenge we collectively face.
Keywords: Climatic changes -- Social aspects.; Climatic changes -- Political aspects.; Energy policy -- Environmental aspects.; elektronické knihy; electronic books